A systematic review of educational resources for teaching patient handover skills to residents - Masterson, Mark F; Gill, Richdeep S; Turner, Simon R; Shrichand, Pankaj; Giuliani, Meredith (Canadian Medical Education Journal, 2013)
<!--[if gte mso 9]> Normal.dotm 0 0 1 212 1211 ubc 10 2 1487 12.256 <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--StartFragment--> <p class="MsoNormal" style="line-height: 200%; mso-pagination: none; tab-stops: 28.0pt 56.0pt 84.0pt 112.0pt 140.0pt 168.0pt 196.0pt 224.0pt 252.0pt 280.0pt 308.0pt 336.0pt; mso-layout-grid-align: none; text-autospace: none;"> Background: As physicians reduce their work hours, transfer of patient care becomes more common; this is a time of heightened risk to patients. Training in patient handover skills may reduce this risk. The objective of this study was to systematically review the literature regarding education models available to teach handovers skills to healthcare professionals. Methods: A systematic review was conducted to identify published educational resources on patient handover skills. Two investigators independently reviewed publications for inclusion/exclusion. A third reviewer resolved any disagreement. Included papers contained an educational resource for teaching handover skills to any health profession in any patient population. Papers were rated on a previously described 4 point scale for quality. Results: 1746 papers were identified, of which twelve met the inclusion criteria These studies presented information on educational curricula, simulation technologies and didactic sessions. The most common educational method was simulation or role-playing, which is better received by learners than didactic sessions. Teaching handover practices makes residents feel more confident in their handover, and residents receiving adequate handover are more comfortable with their duties. Conclusions: Although data are limited, effective training models for handover skills have been described in the literature. Residents and other healthcare practitioners should receive training in handover to improve practitioner comfort and patient care.